Peningkatan Kualitas Kemasan Teh Bunga Telang Melalui Introduksi Teknologi Mesin Continuous Band Sealer - Khomah, Isti; Kusnandar, Kusnandar; Harisudin, Mohamad; Riptanti, Erlyna Wida; Setyowati, Nuning; Qonita, Raden Rara Aulia (Jurnal Pengabdian UNDIKMA, 2024)
This community service activities aim to introduce continuous band sealer machine technology to improve the quality of butterfly pea flower tea product packaging from Idako Sukses Mandiri MSMEs. The implementation of this community service uses participatory and mentoring methods. Activities are evaluated using before-after evaluation and descriptive analysis. The results of the service show that the Continous Band Sealer Machine has a positive impact on business sustainability. The Continous Band Sealer Machine can overcome the problems of MSMEs with limited production equipment in terms of packaging. Idako Sukses Mandiri MSMEs can use the machine well, and they will be more experienced and skilled. The positive impact can be seen from the quality of the packaging sealing; the sealing time becomes faster with a large amount, so the time used becomes efficient.